2013
DOI: 10.1111/acfi.12061
|View full text |Cite
|
Sign up to set email alerts
|

Accounting and Finance: authorship and citation trends

Abstract: Accounting and Finance (A&F ) has experienced a surge in published research in the last decade. The analysis here reveals a marked increase in the number of published articles in A&F since 2003, a distinct trend for published papers to have a larger number of authors, a significant and stable contribution by the top 5 Australian accounting/finance departments, as well as a notable increase in contribution from non-US foreign universities, particularly those located in the UK, Canada, Hong Kong, Singapore and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 68 publications
(35 reference statements)
4
33
0
Order By: Relevance
“…() found that the percentage of co‐authored articles in accounting research increased from 58.5% in 1991 to 72.3% in 2005 in 24 academic accounting journals. Gaunt () also observes a clear trend from single to dual authorship in the 1990s; however, since 2000 there has been a shift from both single and dual authorship to three or sometimes four authors. A recent study by Andrikopoulos and Kostaris () similarly detects a substantial increase in co‐authorship rates within major accounting journals over the period 1985–2014.…”
Section: Literature Reviewmentioning
confidence: 98%
See 4 more Smart Citations
“…() found that the percentage of co‐authored articles in accounting research increased from 58.5% in 1991 to 72.3% in 2005 in 24 academic accounting journals. Gaunt () also observes a clear trend from single to dual authorship in the 1990s; however, since 2000 there has been a shift from both single and dual authorship to three or sometimes four authors. A recent study by Andrikopoulos and Kostaris () similarly detects a substantial increase in co‐authorship rates within major accounting journals over the period 1985–2014.…”
Section: Literature Reviewmentioning
confidence: 98%
“…). Another reason that may motivate academics to establish co‐authorships are academic institutions that measure individual academic performance by publication in peer‐reviewed journals with little distinction between whether those articles are published by a sole author or with a co‐author (Gaunt ). Therefore, academics can achieve the same benefit irrespective of the percentage of their contribution to an article (Nathan et al.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations